SAT0212 Bone and joint scan as compared to joint clinical evidence. (1st June 2001) - Venditti, C; Peluso, R; Cimmino, M; De Luca Bossa, R; Loi, G; Spanò, A; Del Puente, A; Oriente, P
Abstract : Background: Bone and joint scan using 99mTc-MDP is often used in rheumatologic practice, but there is little data on its effective relevance in evaluating chronic articular inflammatory diseases. Objectives: The aim of this work has been to compare bone scan results against clinical evidence of joint inflammatory involvement, evaluating with both approaches the number of affected joints (NAJ) in a group of patients with rheumatoid arthritis (RA) or osteoarthritis (OA). Methods: Bone scan was carried out in 75 consecutive patients (44 RA, 31 OA). The nuclear medicine specialist indicated in the report the list of joints showing uptake. In the same patients (without knowing the results of scintigraphy) a rheumatologist diagnosed the NAJ on the basis of clinical signs of inflammation. Then the patients were stratified in 2 * 2 tables according to the prevalence of clinical evidence or scintigraphic uptake. Results: The distribution was found to be not significant (chi-square = 1.6, p = 0.2). The percentage of patients without uptake was only 5.3%. In 33 patients (44%) no clinical evidence was observed. Among these, 30 showed articular uptake (in an average of 7.0 * 4.6 joints). Considering only the patients with clinical evidence, the subjects with articular uptake were 41 out of 42 (97.6%) with an average of 8.6 * 4.6 involved joints. In these patients the ratio between number of joints with uptake and number of joints with clinical evidence (ratio uptake/clinical) was then calculated for each subject. Such a ratio resulted in an average of 2.9 * 3.6. These results were also confirmed analysing the data by sex, disease (RA or OA) and class of therapy. We then decided to assess if the greater prevalence of involved joints obtained with bone scan was correlated with an increase of inflammatory indexes. Taking into consideration the patients with clinical evidence, we performed multiple regression analysis using as dependent variable in distinct models the ratio uptake/clinical, the number of joints with clinical evidence and the number of joints showing uptake. The inflammatory indexes (ESR and CRP) were used as independent variables and age, sex, diagnosis and therapy were used as covariates. The uptake/clinical ratio did not show any significant correlation. The number of joints with clinical evidence correlates with ESR, those ones showing uptake correlates only with age, both with direct correlation. Conclusion: The data obtained indicates that the articular scintigraphic uptake in AR and OA, on average, highlights a significantly higher number of joints involved as compared to the clinical test. It still remains to be defined if this is an overestimation related to the characteristics of the scan or if it is the sign of a higher sensibility in highlighting the inflammation location. An element of caution against the second hypothesis is established by the absence of correlation with the inflammatory indexes.